Sociology and the World's Religions - Hamilton, M. author. aut Link
VIII, 273 p.
Keywords: Sociological and related studies of systems of religion tend to be fragmented. This book brings together and assesses a diverse range of substantive sociological, anthropological and social-psychological scholarship dealing with the broad spectrum of religious belief, experience and behaviour from the work of anthropologists on the religions of tribal and pre-industrial peoples to explorations of the origins, development and impact of the great world religions. The book will have particular appeal not only in the fields of sociology, social anthropology, but also religious studies.